Reagent Filming for Universal Point‐of‐Care Diagnostics. Issue 12 (7th October 2021) - Han, Gyeo‐Re; Jang, Hyungjun; Ki, Hangil; Lee, Hoyeon; Kim, Min‐Gon
Abstract: Simplifying assays while maintaining the robustness of reagents is a challenge in diagnostics. This problem is exacerbated when translating quality diagnostic assays to developing countries that lack resources and infrastructure such as trained health workers, high‐end equipment, and cold‐chain systems. To solve this problem, in this study, a simple solution that films assay reagents to simplify the operation of diagnostic assays and preserve the stability of diagnostic reagents without using cold chains is presented. A polyvinyl‐alcohol‐based water‐soluble film is used to encapsulate premeasured and premixed reagents. The reagent film, produced through a simple and scalable cast‐drying process, provides a glassy inner matrix with abundant hydroxyl groups that can stabilize various reagents (ranging from chemicals to biological materials) by restricting molecular mobility and generating hydrogen bonds. The reagent film is applied to an enzymatic glucose assay, a high‐sensitivity immunoassay for cardiac troponin, and a molecular assay for viral RNA detection, to test its practicability and universal applicability. The film‐based assays result in excellent analytical/diagnostic performance and stable long‐term reagent storage at elevated temperatures (at 25 or 37 °C, for six months), demonstrating clinical readiness. This technology advances the development and distribution of affordable high‐quality diagnostics to resource‐limited regions. Abstract : Simplifying assays while maintaining reagent robustness is a key challenge in point‐of‐care diagnostics. This work presents a simple and robust framework that films premeasured diagnostic reagents using a polyvinyl‐alcohol‐based water‐soluble matrix. Reagent filming can stabilize labile reagents without a cold chain and be universally applied to various clinical assays, advancing the translation of quality diagnostics to resource‐limited regions.